2021
DOI: 10.1159/000519835
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Immunological Features of Inflammatory Demyelinating Diseases of the Central Nervous System

Abstract: Objective: The immunological features between neuromyelitis optica spectrum disorder (NMOSD), multiple sclerosis (MS), and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD), lacked systemic comparisons. Accordingly, we aimed to investigate immunological differences between NMOSD, MS, and MOGAD. Methods: Patients with MOGAD, MS, and NMOSD who received immunological tests including cytokine profiles and cytometry analysis of the lymphocyte subgroups were retrospectively reviewed and divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Therefore, whether the increase in monocytes and lymphocytes means the treatment is effective needs further research. Finally, more attention should be paid to the pathological changes of NMOSD as the decline of NK cells was also shown to be absent in MS ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether the increase in monocytes and lymphocytes means the treatment is effective needs further research. Finally, more attention should be paid to the pathological changes of NMOSD as the decline of NK cells was also shown to be absent in MS ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We removed duplicates and screened 308 studies. Finally, we included 6 articles [20][21][22][23][24][25]…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 2 shows the general characteristics of included studies. Ten studies reported the association between NLR and NMOSD [16,[19][20][21][22][23][24][25][26][27]. All of them were written in English and were designed retrospective.…”
Section: Overviewmentioning
confidence: 99%
“…All of them were written in English and were designed retrospective. Seven studies were conducted in China [16,[20][21][22][25][26][27] , one in the United Kingdom [19], one in Germany and Austria [23], and one in Latin America [24].…”
Section: Overviewmentioning
confidence: 99%